2012
DOI: 10.1063/1.4772546
|View full text |Cite
|
Sign up to set email alerts
|

Extensive study of giant magnetoresistance properties in half-metallic Co2(Fe,Mn)Si-based devices

Abstract: Fully epitaxial Co 2 Fe x Mn 1Àx Si(CFMS)/Ag/Co 2 Fe x Mn 1Àx Si current-perpendicular-to-plane giant magnetoresistive devices with various Fe/Mn ratios x and top CFMS layer thicknesses t CFMS were prepared. The highest magnetoresistance (MR) ratios, 58% at room temperature and 184% at 30 K, were observed in the sample with x ¼ 0.4 and t CFMS ¼ 3 nm. Enhancement of interface spinasymmetry was suggested for x ¼ 0.4 compared with that at x ¼ 0. A MR ratio of 58% was also observed even in a very thin trilayer str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(78 citation statements)
references
References 25 publications
(41 reference statements)
3
73
0
Order By: Relevance
“…High magnetoresistance (MR) ratios and large spin accumulation signals in spintronic devices using Co-based Heusler alloys clearly reflect the half-metallic nature of these alloys [17][18][19][20][21][22][23][24]. Recently, a very high value of spin polarization was observed for Co-based alloys at low temperatures, but a strong degradation in the transport properties was seen at room temperature [15,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High magnetoresistance (MR) ratios and large spin accumulation signals in spintronic devices using Co-based Heusler alloys clearly reflect the half-metallic nature of these alloys [17][18][19][20][21][22][23][24]. Recently, a very high value of spin polarization was observed for Co-based alloys at low temperatures, but a strong degradation in the transport properties was seen at room temperature [15,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…HMF materials have potential applications as spin polarized current sources for current perpendicular to plane giant magnetoresistance (CPP-GMR) [17][18][19], magnetic tunnel junctions (MTJ) [20,21], non-local spin-valve (NLSV) devices [22,23] and spin injectors to semiconductors [24]. High magnetoresistance (MR) ratios and large spin accumulation signals in spintronic devices using Co-based Heusler alloys clearly reflect the half-metallic nature of these alloys [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Co2Fe0.4Mn0.6Si (CFMS) is another fullHeusler alloy exhibiting high spin polarization of conduction electrons. In fact, the CPP-GMR devices with CFMS | Ag | CFMS showed the MR ratios larger than CMS | Ag | CMS 24) . Thus, CFMS is also a candidate material for developing high performance STO 25,26) .…”
Section: Spin Torque Oscillator Using Co-based Heusler Alloymentioning
confidence: 99%
“…Sakuraba et al demonstrated an MR ratio of 58% at RT and 184% at 30 K in Co 2 Fe 0. 4 Mn 0.6 Si/Ag Co2Fe0.4Mn0.6Si/Ag CPP-SV [13]. Moreover, a number of CPP-SVs employing a Heusler alloy as the spin injector, such as Co2MnSi/Ag, Co2FeAl0.5Si0.5/Ag, and Co2FeGa0.5Ge0.5/Ag, also obtained high MR ratios [14,15].…”
Section: Introductionmentioning
confidence: 97%